2016
DOI: 10.1155/2016/4872473
|View full text |Cite
|
Sign up to set email alerts
|

Strongyloides stercoralisInfection in Alcoholic Patients

Abstract: The course of Strongyloides stercoralis infection is usually asymptomatic with a low discharge of rhabditoid larva in feces. However, the deleterious effects of alcohol consumption seem to enhance the susceptibility to infection, as shown by a fivefold higher strongyloidiasis frequency in alcoholics than in nonalcoholics. Moreover, the association between S. stercoralis infection and alcoholism presents a risk for hyperinfection and severe strongyloidiasis. There are several possible mechanisms for the disrupt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
39
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(42 citation statements)
references
References 122 publications
(153 reference statements)
0
39
0
3
Order By: Relevance
“…In this case series, few patients had risk factors for strongyloidiasis other than HTLV-1 infection, including recent steroid use (3), organ transplant (4), or cirrhosis (27,28). In areas with HTLV-1 endemicity, HTLV-1 infection is the major risk factor for both chronic strongyloidiasis and dissemination (29).…”
Section: Discussionmentioning
confidence: 88%
“…In this case series, few patients had risk factors for strongyloidiasis other than HTLV-1 infection, including recent steroid use (3), organ transplant (4), or cirrhosis (27,28). In areas with HTLV-1 endemicity, HTLV-1 infection is the major risk factor for both chronic strongyloidiasis and dissemination (29).…”
Section: Discussionmentioning
confidence: 88%
“…Alcoholic individuals usually practice lower hygienic habits, and the consequence of this can be demonstrated by the elevated frequency of intestinal parasites [ 9 , 10 , 11 ]. In this study, most individuals lived in the state capital city, Salvador, and had access to a sewage system, paved streets, daily garbage collection, running water, and a bathroom at home.…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of S. stercoralis infection in alcoholic patients is reported to be approximately five times higher than that in the general population [ 9 , 10 , 11 ]. One possible mechanism includes an alteration in the hypothalamic–pituitary–adrenal (HPA) axis function, raising the levels of endogenous corticosteroids and its metabolites, which resemble an ecdysteroid hormone that regulates the fertility of S. stercoralis parthenogenetic females, induces the transformation of rhabditiform to infective filariform larvae, and increases the autoinfection rate [ 11 ]. A recent study by our group has demonstrated that increased endogenous cortisol levels is directly related to parasite load [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Several immunosuppression-related risk factors for Strongyloides hyperinfection have been described including the use of corticosteroids and other immunosuppressants, HTLV-1 infection, organ transplantation, and hematologic malignancies 1 , 7 . Other predisposing factors are malnutrition, alcoholism, and diabetes mellitus 1 , 8 , 9 . These three conditions were present in the patient whose case we report.…”
Section: Discussionmentioning
confidence: 99%